Application of Group Guidance to Improve Communication Skills of Students - Tarmizi Tarmizi; Mesiono Mesiono; Adilah Noursyarief Karafah (Universitas Islam Negeri (UIN) Sumatera Utara, 2019)
In analyzing researchdata researchers use data reduction, data presentation and provide conclusions. This study raisednine children who have difficulty communicating. The guidance and counseling (BK) has groupguidance services to improve student communication skills, develop student outreach and so on.Researchers use group guidance to improve student communication skills, by encouragingstudents to communicate actively in group guidance activities, it can trigger students' desire to beable to express their opinions. The group guidance process was carried out several times to getmaximum results.